Evaluation of Abnormal Limb Conformation in Jumping Thoroughbred Horses - MOSTAFA, M. B.; SENNA, N. A.; ABU-SEIDA, A. M.; ELEMMAWY, Y. M. (Journal of the Hellenic Veterinary Medical Society, 2019)
Subjective, objective and photographic image using software Auto CAD programme were used for evaluation of limb conformation in 51 jumping thoroughbred horses. The abnormal limb conformations were included: standing under in front (58%), steep shoulder (55%), carpus valgus (45%), calf knee (31%), standing under behind (31%), short pelvis (31%) and straight hocks (16%). Linear and angular limb measurements showed standing under in front had increased elbow joint lateral angle, and decreased fore fetlock joint lateral angle. Steep shoulder displayed a significant increase (P< 0.05) in shoulder joint lateral angle and significant decrease in forearm front length. calf knee horses had significant decrease in the lateral angle of carpus joint. Short pelvis had a significant decrease in lateral length of pelvis and significant increase in croup angle and stifle joint lateral angle. Straight hocks showed the lateral length of both pelvis and gaskin showed a significant decrease and significant increase in the stifle joint lateral angle. Therefore, the current use of linear and angular measurements in relationships to abnormal limb conformation in the present study will allow for estimation of the future performance and soundness in jumping thoroughbred horses. In addition can be considered for selection athletic horse with less risk of lameness.